MENAVIGASI LABIRIN POLITIK KONTEMPORER: Analisis Komparatif Teori Politik Pada Agama Islam dan Kristen - Rosyidah, Fatimah Nurul; Hakim, Azka Ibadil; Bahauddin, Bahauddin; Shinta, Nayshilla Dea; Putri, Salsabila Nuraulia; Ramadani, Siti Isnaini (UIN ANTASARI BANJARMASIN, 2023)
This study examines the political relationship between Islam and Christianity in the context of contemporary politics, focusing on the political theories of both religions. The background of this research lies in the complexity of the relationship between religion and politics, which has become increasingly relevant in the era of globalization, where Islam and Christianity play significant roles in global political dynamics. The study employs a qualitative method based on a literature review from various credible sources, such as books, scholarly articles, and expert works. Data analysis is conducted through the categorization of key themes, including the role of religion in the public sphere, the relationship between religion and the state, and efforts to foster interfaith dialogue. The findings reveal that Islamic political theory emphasizes values of justice, consultation, and welfare, while Christian political theory focuses more on integrating moral values into public policies. Despite differing approaches, both traditions hold the potential to promote interfaith dialogue and tolerance. A comparison of Islamic and Christian political theories highlights opportunities to create harmony through the application of concepts such as inclusivism and tolerance in social and political interactions. This research provides a significant contribution to the study of the relationship between religion and politics and supports the creation of inclusive dialogue amid cultural and religious diversity.